The Effect Of Transformational Leadership On Employee Performance And Organizational Commitment - Aman Erianto; Ardiani Auliya Nurhasanah; M. Hari Sahrul Fauzan; Nadia Fajar Nabila; Yola Ervilia; Recky Recky (International Journal of Health Engineering and Technology, 2026)
Leadership plays an important role in determining organizational success in achieving its goals. In today’s dynamic business environment, organizations require adaptive leadership capable of improving employee performance and organizational commitment. This study aims to analyze the effect of transformational leadership on employee performance and organizational commitment. This study employed a qualitative approach using a literature review method. Data were collected from scientific sources, including books, national and international journals, and relevant academic publications. The selected literature was analyzed descriptively to identify patterns and relationships between transformational leadership, employee performance, and organizational commitment. The findings indicate that transformational leadership has a positive and significant effect on employee performance and organizational commitment. Through its four main dimensions, namely idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration, transformational leadership creates a conducive work environment and encourages employees to perform beyond expectations. The study also found that the influence of transformational leadership can occur directly or indirectly through mediating variables such as organizational commitment, employee engagement, employee empowerment, self-efficacy, and organizational citizenship behavior. In conclusion, transformational leadership is an effective strategy for improving employee performance, strengthening organizational commitment, and supporting sustainable organizational success.